2015
DOI: 10.3109/01902148.2015.1054053
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone protects rats and human pulmonary alveolar epithelial cells against hyperoxia injury: heme oxygenase-1 and PI3K/Akt pathway may be involved

Abstract: This study indicates that edaravone protects rats and human pulmonary alveolar epithelial cells against hyperoxia-induced injury and the antioxidant effect may be related to upregulation of HO-1, which is regulated by PI3K/Akt pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…ZnPP has been reported to reduce HO-1 expression and suppress HO-1 activity [34,35,58,59], and has been widely used for HO-1-related research [35,58,59]. Our present study showed that the expression and activity of HO-1 was downregulated by ZnPP pretreatment of MSCs-HO-1.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…ZnPP has been reported to reduce HO-1 expression and suppress HO-1 activity [34,35,58,59], and has been widely used for HO-1-related research [35,58,59]. Our present study showed that the expression and activity of HO-1 was downregulated by ZnPP pretreatment of MSCs-HO-1.…”
Section: Discussionsupporting
confidence: 60%
“…These results suggested that enhanced endothelial HO-1 expression and activity also contributed to the beneficial effects of co-culture with MSCs-HO-1. Multiple kinase signaling pathways, such as phosphatidylinositol 3-kinase/p38 and extracellular-signal-regulated kinase/c-Jun N-terminal kinase pathways, have been reported to be involved in HO-1 inducible expression [35,39]. However, further investigations are still needed to reveal which kinase signaling pathways are involved the promotive effect of MSCs-HO-1 on endothelial HO-1 expression and activity following LPS-simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that AEC II cells treated with hyperoxia had enhanced cell apoptosis, decreased MDA levels, and increased SOD activity. Therefore, we speculated that apoptosis of hyperoxia-treated cells is caused by increased oxidative stimuli in AEC II cells, which is consistent with a previous study [ 33 ]. However, interestingly, CGRP treatment inhibited hyperoxia-caused AEC II cells apoptosis and hyperoxia-triggered oxidative stress, including changes in MDA, SOD, and ROS.…”
Section: Discussionsupporting
confidence: 92%
“…These results demonstrated that the conditioned medium of hfPMSCs could activate the Nrf-2 signaling pathway and protect the cells from oxidative injury. Consequently, many signaling pathways, such as PI3/AKT/ERK pathways, have been reported to regulate HO-1 [37, 38]. Therefore, further studies still need to investigate signaling pathways playing key roles in preventing H 2 O 2 -induced oxidative injury in primary lung epithelial cells in vitro and animal models in vivo .…”
Section: Discussionmentioning
confidence: 99%